Um estudo sobre a localização industrial do Estado de São Paulo - Dias, Diego Figueiredo (2008)
The present study aimed to make an analysis of the industry location from Sao Paulo state by the Tax Value Added to each city for 2005 through the use of spatial econometrics techniques. By making use of such techniques, we intended to verify the spatial components behavior like spatial autocorrelation and heterogeneity. Firstly, it has been used Exploratory Spatial of Data Analysis (ESDA) to validate the spatial autocorrelation among the Sao Paulo's state cities, considering the industrial TVA 2005. The results demonstrated the existence of spatial autocorrelation among the cities and that's the biggest TVA are in the region of Ribeirão Preto, metropolitan region of Campinas (MRC), metropolitan region of Sao Paulo (MRSP) and "Vale do Paraíba" region. In order to verify the existence of clusters using the local's Moran I, it was noticed two cluster's type high-high as well as two cluster's type low-low, where the first high-high is located at the MRSP and the second one is located at the RMC. The two cluster's type low-low embrace the Southwest, West and Northwest cities of São Paulo state. The West and Northwest cities are strongly characterized by farming. It was not possible to estimate a perfect model for the industry location of Sao Paulo state due to the weakness of the information and data available when applied the coefficient of regression determination.